Research handbook on implementation of human rights in practice - Murray, Rachel, 1980-; Long, Debra (Research handbooks in human rights series, 2022)
"Building upon the growing body of scholarship on the factors and actors that influence the extent to which states implement human rights law, this cutting-edge Research Handbook takes an interdisciplinary approach to exploring the roles of actors within supranational human rights bodies, the decisions and judgements they make and the tools they use to facilitate human rights implementation. Eminent scholars and practitioners in the field reflect on why states implement, or fail to implement, obligations and decisions from the supranational level. The Handbook reviews the relevant terminology, recent trends and the theoretical and methodological perspectives and strategies, before rethinking these explanations and offering original scholarship on human rights implementation. Chapters then consider the roles and interplay of various domestic and international actors involved in human rights implementation, including parliaments, national courts, civil society and treaty bodies. The Handbook concludes by assessing tools of implementation, including monitoring systems, the role of negotiations and diplomacy, compliance hearings and the use of IT for compliance. Exploring the entire process of human rights law implementation from recommendation to execution to follow up, this comprehensive Handbook will be an invaluable resource to students, scholars and practitioners interested in the decisions and judgements behind the implementation of human rights law"--